Extended High Frequency Hearing, but Not Tinnitus, Is Associated With Every-Day Cognitive Performance - Waechter, Sebastian; Wilson, Wayne J.; Magnusson, Måns; Brännström, K. Jonas (Frontiers in Psychology, 2022)
Research into the potential associations between tinnitus and cognition has investigated specific cognitive domains in laboratory settings despite adults with tinnitus reporting broad cognitive difficulties in every-day life. To address this limitation, the present study compared performance and perceived exertion on a visual office-like task in 38 adults with tinnitus (19 with normal hearing and 19 with hearing loss) and 38 adults without tinnitus (19 with normal hearing and 19 with hearing loss) matched for age, sex and educational background. All participants were also assessed for hearing, anxiety and depression, and participants with tinnitus were also assessed for tinnitus handicap. No associations were found between tinnitus and performance and perceived exertion on the visual office-like task when corrected for hearing thresholds, anxiety, and depression. The correction for extended high frequency average (10, 12.5, 14 and 16 kHz) hearing threshold was significant for performance but not perceived exertion on the visual office-like task. Overall, the results showed extended high frequency hearing, but not tinnitus, was associated with every-day cognitive performance.